An LC/MS/MS method for quantifying 25-hydroxyvitamin D3 in finger-prick plasma sample prepared by DEMECAL® micro plasma separation device: toward mail-in assessment of vitamin D status - Maeda, Kodai; Sakamoto, Kyoka; Ito, Eiko; Sugimoto, Shinya; Tajima, Shingo; Sasahara, Takahisa; Kawamura, Shunji; Yaegashi, Kazuo; Higashi, Tatsuya (Analytical and bioanalytical chemistry, 2025)
A mail-in assessment of vitamin D status will make it possible for the subjects to early detect any vitamin D insufficiency/deficiency at their homes, thus leading to a better management of their health. In this study, a liquid chromatography/electrospray ionization-tandem mass spectrometry (LC/ESI–MS/MS) method was developed and validated for quantifying 25-hydroxyvitamin D 3 [25(OH)D 3 ], which is the established marker of the vitamin D status, in the finger-prick blood plasma sample prepared by the DEMECAL ® device. By using the DEMECAL ® device, the subjects can collect their finger-prick blood at their homes and immediately separate the plasma from the blood by themselves. The DEMECAL ® -based procedure had advantages over the venipuncture- and dried blood spot-based procedures because it is less invasive and a medical professional-free blood collection, and no need to be concerned with the heterogeneity of the analyte distribution in the sample. The developed LC/ESI–MS/MS method enabled the precise and accurate quantification of 25(OH)D 3 and provided the lower limit of quantification of 0.10 ng/mL in the diluted plasma sample due to the derivatization with 4-(4-dimethylaminophenyl)-1,2,4-triazoline-3,5-dione. 25(OH)D 3 was stable in the plasma sample prepared by the DEMECAL ® device at room temperature (23–27 °C) for 7 days (simulated condition in the mail) and at 4 °C for 30 days (simulated condition during storage at a laboratory). The measured 25(OH)D 3 concentrations by the DEMECAL ® -based procedure well agreed with those by the conventional venipuncture-based procedure. These results demonstrated that the derivatization-LC/ESI–MS/MS combined with the DEMECAL ® -based sample preparation is a promising procedure for the mail-in assessment of the vitamin D status. Graphical Abstract